Transcriptomic and metabolomic analyses reveal the molecular mechanisms by which long-day photoperiods promote flowering in Gossypium hirsutum L. - Zhang, Ning; Liu, Yujie; Lu, Yuli; Zhou, Zhonghua; Wang, Qiming; Liu, Aiyu; Tu, Xiaoju (Frontiers in Plant Science, 2025)
Photoperiod is a crucial environmental cue that regulates flowering time in plants, playing a vital role in crop adaptability and early maturity. However, the molecular mechanisms underlying photoperiod-regulated flowering in cotton (Gossypium hirsutum L.) remain unclear. In this study, cotton plants were exposed to different photoperiod treatments during the seedling stage. Phenotypic evaluation, transcriptomic sequencing, and metabolomic profiling were integrated to systematically investigate the effects of photoperiod on flowering time and the associated molecular and metabolic regulatory pathways. The results showed that long-day treatments significantly accelerated budding and flowering in cotton, advancing by 20 and 17 days, respectively, compared to short-day conditions. Transcriptome analysis identified numerous differentially expressed genes (DEGs) involved in photoperiod response, hormone signaling, and metabolic regulation. Weighted Gene Co-expression Network Analysis (WGCNA) further revealed that key photoperiod-related genes, including GhFKF1, were upregulated under long-day conditions and formed co-expression networks with flowering regulators. Integrated transcriptomic and metabolomic analyses revealed significant enrichment in glycerophospholipid metabolism, α-linolenic acid metabolism, and flavonoid biosynthesis pathways. Long-day treatment suppressed the expression of key genes and precursors involved in jasmonic acid biosynthesis, while simultaneously upregulating genes involved in flavonoid biosynthesis, leading to increased accumulation of metabolites such as myricetin. Therefore, we propose a theoretical model in which long-day treatment during the seedling stage integrates hormonal and photoperiodic signals by upregulating the expression of the GhFKF1 gene. This regulation may contribute to the initiation of flowering by simultaneously suppressing jasmonic acid biosynthesis and activating the flavonoid biosynthetic pathway. Our findings offer a theoretical foundation and a novel perspective for understanding the photoperiodic response and molecular mechanisms underlying early maturation in cotton.